Pancasila Sebagai Kompas Moral Pergaulan Siswa/Siswi SMAIT Rahmaniyah Boarding School - Tegar Mei Prihatna; Wanda Maliya; Alya Almas Az-Zahra; Aulia Rahma; Nur Aini Ramadhani; Fahri Fahlevi; Abdul Karim Naufal Dalimunthe; Mochdar Soleman, S.IP., M.Si. (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2026)
Adolescent social interaction plays a significant role in shaping character and moral development, particularly amid the rapid advancement of technology and social media, which expose young people to both positive and negative influences. In this context, the values of Pancasila serve as an essential moral foundation to guide adolescents in social interactions, decision-making, and responsible behavior. This study aims to analyze the forms of students' social interactions, examine their influence on moral development, and investigate the role of Pancasila as a moral compass among students at SMAIT Rahmaniyah Boarding School. A descriptive qualitative approach was employed, with data collected through observation, semi-structured interviews, and documentation. The participants consisted of 12 respondents, including 10 students and 2 teachers, selected using purposive sampling. The findings reveal that the environment promotes. positive social interactions characterized by tolerance, cooperation, mutual assistance, responsibility, social awareness, and deliberative problem-solving. Such interactions contribute significantly to students' character and moral development, although challenges related to social media influence and verbal bullying remain evident. Furthermore, the implementation of Pancasila values through classroom learning, dormitory life, student organizations, and character-building programs strengthens students' social behavior. The study concludes that Pancasila functions as an effective moral compass, guiding students to think, behave, and interact in accordance with Indonesia's fundamental moral and cultural values.